Respuesta :
-10p+9p= 12
⇒ (-10+9)*p= 12 (distributive property)
⇒ -1*p= 12
⇒ -p= 12
⇒ p= -12
Final answer: p=-12~
⇒ (-10+9)*p= 12 (distributive property)
⇒ -1*p= 12
⇒ -p= 12
⇒ p= -12
Final answer: p=-12~
we add like terms
to understand this user the distributive property in reverse like this
ab+ac=a(b+c) so we have
-10p+9p=(-10+9)p
we add the terms in the parenthsees
-10+9=9-10=-1
so we have
-1p=12
multiply both sides by -1
p=-12
to understand this user the distributive property in reverse like this
ab+ac=a(b+c) so we have
-10p+9p=(-10+9)p
we add the terms in the parenthsees
-10+9=9-10=-1
so we have
-1p=12
multiply both sides by -1
p=-12